Effect of magnetic field on the steady nanofluid flow past obstacle - Khelili, Yacine; Bouakkaz, Rafik (Physics and Chemistry of Solid State, 2021)
The fluid flow and heat transfer of a nanofluid past a circular cylinder in a rectangular duct under a strong transverse magnetic field is studied numerically using a quasitwo-dimensional model. Transition from laminar flow with separation to creeping laminar flow is determined as a function of Hartmann number and the volume fraction of nanoparticle, as are critical Hartmann number, and the heat transfer from the heated wall to the fluid. Downstream cross-stream mixing induced by the cylinder wake was found to increase heat transfer. The successive changes in the flow pattern are studied as a function of the Hartmann number. Suppression of vortex shedding occurs as the Hartmann number increases.